Space experience or experience in space? - Schneller, István (4D Journal of Landscape Architecture and Garden Art, 2010)
The spaces of our cities, together with their spatial characteristics, are stolen by the large surface-area commercial units or closed buildings created in the middle of vast asphalt wastelands. They privatize or from a different point of view monopolize the spatial configurations of the city together with the agora-type, or encounter-oriented, public spaces that have evolved through history and are the essence of urbanity. Privatization is nőt even the proper word, fór what happens to these spaces. The public spaces formerly having a far-reaching degree of freedom are manipulated, and put to be at the service of a well definable goal: consumption.